Association Between Early Postpartum Counseling and Breastfeeding Success Rates: A Cross-Sectional Study - Fouzia Jan, Nadia Munir, Hanana Hameed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Early initiation of breastfeeding within the first hour of life and exclusive breastfeeding for six months are essential for optimal infant health and maternal well-being. Despite global recommendations, breastfeeding practices in Pakistan remain suboptimal due to social, cultural, and systemic barriers. Early postpartum counseling may play a critical role in improving these outcomes, yet local evidence is limited. Objective: To evaluate the impact of early postpartum counseling on breastfeeding initiation, exclusivity, maternal knowledge, and satisfaction. Methodology: This cross-sectional study was conducted at a tertiary care hospital in Quetta, Pakistan, from November 2022 to June 2023. A total of 100 postpartum women were divided into two equal groups: Group A received structured breastfeeding counseling within six hours of delivery, while Group B received routine care without counseling. Outcomes assessed included time to breastfeeding initiation, exclusivity at six weeks, maternal knowledge score (0–10), satisfaction level (Likert scale), and need for formula supplementation. Data were collected through structured interviews and analyzed using SPSS version 25. Chi-square and t-tests were applied where appropriate. Results: Early initiation within one hour was significantly higher in Group A (86%) than in Group B (52%) (p = 0.001). Exclusive breastfeeding at six weeks was 76% in Group A versus 44% in Group B (p = 0.002). Maternal knowledge and satisfaction scores were significantly higher in the counseled group (p < 0.001), with lower formula use (18% vs. 48%, p = 0.003). Conclusion: Early postpartum counseling significantly improves breastfeeding outcomes. Integrating structured counseling into postnatal care is strongly recommended. Keywords: Breastfeeding, postpartum counseling, exclusive breastfeeding, maternal knowledge, infant nutrition.